A180: A Population Management Tool for Proactive Care of Juvenile Idiopathic Arthritis in the Pediatric Rheumatology Care and Outcomes Improvement Network. Issue 11 (March 2014) - Ardoin, Stacy P.; Bingham, C. April; Gottlieb, Beth S.; Laxer, Ronald M.; Passo, Murray H.; Lovell, Daniel; Weiss, Jennifer E.; Vora, Sheetal S.; Lee, Tzielan C.; Griffith, Nancy; DeWitt, Esi Morgan
Abstract : Background/Purpose: The Pediatric Rheumatology Care and Outcomes Improvement Network (PR‐COIN) is a multi‐center, quality‐improvement‐focused learning network with a mission of improving outcomes for children and adolescents with juvenile idiopathic arthritis (JIA). PR‐COIN has developed a population management tool which facilitates pro‐active, coordinated health care communications and interventions that can be used in managing JIA patient populations. Methods: The population management tool was developed with information technology expertise to link seamlessly to the PR‐COIN longitudinal registry. Within the population management tool, on demand reports can be generated using participating site or aggregate, network level data according to demographics, clinical features, disease activity levels, patient reported outcomes (functional ability/CHAQ score, arthritis related pain), medication use, and quality indicators. Drill down capability enables identification of patients. Results: Currently, data from 8 sites, 1161 patients, and 5334 clinical encounters are included in the population management tool (Table 1 ). Individual site usage of the population management tool is variable ranging from infrequent use to regular use at monthly population management meetings. The PR‐COIN network is currently developing strategies to promote consistent usage of the tool at sites. Clinicians routinely using information provided through this tool report satisfaction with its functionality and ease of use; furthermore they report enhanced ability to proactively identify and address specific patient needs prior to and during clinic visits, optimizing care. Conclusion: The population management tool allows real‐time feedback to sites regarding overall JIA population and individual patient status. Customized, "on demand" population measurement and quality improvement reports generated by the network and participating sites and can be used to identify gaps in patient care and at‐risk subpopulations that may benefit from more intensive or between‐visit care. Current efforts include developing a care stratification scores that can assist in identifying at risk JIA subpopulations and provision of individual patient reports that can be used to assist in pre‐visit planning. Future goals include providing feedback to individual patients about their disease status compared to local and network aggregate data, and customized educational and interventional tools that can be provided to JIA patients and families. Thus, the PR‐COIN JIA population management tool can be leveraged to improve JIA network and site performance and individual patient care.